Pandangan dan Pengalaman Dosen UIN Alauddin Makassar dalam Upaya Mengantisipasi Gerakan Islam Radikal di Kalangan Mahasiswa - Arifuddin Arifuddin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
This article is intended to fill the gap scholarly studies about radical movements in the university environment. This study is a qualitative research with phenomenological approach involving six (6) lecturers of UIN Alauddin Makassar as a research subject. From the interviews, it has been found out that the lecturers had the same view of radicalism in terms of positive and negative. Apparently, radicalism is growing because it begins with less understanding of religious thoughts among students which is triggered by their immature pattern of thinking as well as their great curiosity. Basically, all respondents consider this issue is a serious and often discussed with their students. Universities and lecturers, therefore, are encouraged to direct and guide the students to avoid the development of radical ideologies.